Eye refraction in doubly exchanged monozygotic twins (2019)
This case study examined the hypothesis that longer outdoor time results in normal vision and refractive status, using unique genetically informative kinships. The participants were the members of 29-year-old doubly exchanged monozygotic male twin pairs from Bogotá, Colombia, in South America. Comprehensive ophthalmological examinations, including uncorrected and corrected visual acuity, refraction and keratometry, and visual life history interviews were undertaken; all examinations were conducted by two ophthalmologists blind to the hypothesis, relatedness, and rearing status of the four participants. Normal uncorrected vision and refractive status were present in the two rural-raised, unrelated brothers, relative to their urban-raised counterparts. Uncorrected visual acuities were 20/160 and 20/200 for the city-raised twins and 20/20 and 20/30 for the country-raised twins. Premature birth, low birth weight, computer use, and reading time could not explain these differences. It was concluded that time spent outdoors appears to be a significant factor in the development of myopia, reinforcing extant findings via a novel experimental approach.